Using metabolic abnormalities of carriers in the neonatal period to evaluate the pathogenicity of variants of uncertain significance in methylmalonic acidemia - Xiao, Dongfan; Shi, Congcong; Zhang, Yinchun; Li, Sitao; Ye, Yuhao; Yuan, Guilong; Miu, Taohan; Ma, Haiyan; Diao, Shiguang; Su, Chaoyun; Li, Zhitao; Li, Haiyan; et al. (Frontiers in Genetics, 2024)
Objective: To accurately verify the pathogenicity of variants of uncertain significance (VUS) in MUT and MMACHC genes through mass spectrometry, and silico analysis.Methods: This multicenter retrospective study included 35 participating units (ClinicalTrials.gov ID: NCT06183138). A total of 3071 newborns (within 7 days after birth) were sorted into carrying pathogenic/likely pathogenic (P/LP) variant , carrying VUS, non-variant groups. Differences in metabolites among the groups were calculated using statistical analyses. Changes in conservatism, free energy and interaction force of MMUT and MMACHC variants were analyzed using silico analysis.The percentage of carrying VUS cases was 68.15% (659/967). In the MMUT gene variant, we found that the C3, C3/C2, and C3/C0 levels in carrying P/LP variant group were higher than those in the non-variant group (P<0.000) . The conservative scores of carrying P/LP variant group were > 7. C3, C3/C0, C3/C2 values of newborns carrying VUS (c.1159A>C and c.1286A>G) were significantly higher than those of the nonvariant group and the remaining VUS newborns (P<0.005). The conservative scores of c.1159A>C and c.1286A>G calculated by ConSurf analysis were 9 and 7, respectively. Unfortunately, three MMA patients with c.1159A>C died during the neonatal period, their C3, C3/C0, C3/C2, and MMA levels were significantly higher than those of the controls.Common variants of methylmalonic acidemia in the study population were categorized as VUS. In the neonatal period, the metabolic biomarkers of carrying P/LP variant group of the MUT gene were significantly higher than those in the non-variant group. If the metabolic biomarkers of carrying VUS are also significantly increased, combined with silico analysis, the VUS may be elevated to a likely pathogenic variant. The results also suggest that mass spectrometry and silico analysis may be feasible screening methods for verifying the pathogenicity of VUS in other inherited metabolic diseases.